Toll‐like receptors ‐4 and ‐5 in oral and cutaneous squamous cell carcinomas. (22nd July 2014) - Ahmed Haji Omar, Abdirisak; Korvala, Johanna; Haglund, Caj; Virolainen, Susanna; Häyry, Valtteri; Atula, Timo; Kontio, Risto; Rihtniemi, Jarmo; Pihakari, Antti; Sorsa, Timo; Hagström, Jaana; Salo, Tuula
<x xml:space="preserve">Abstract</x> Background Oral squamous cell carcinoma (OSCC) has a worse prognosis than cutaneous squamous cell carcinoma (CSCC). Toll‐like receptor‐ 4 (TLR‐4) and TLR‐5 are transmembrane proteins that recognize endogenous and microbial agents. Their activation has been connected to cancer invasion. Objective The aim was to study the expression of TLR‐4 and TLR‐5 in OSCC and CSCC samples, and the effects of TLR‐5 ligand flagellin on the proliferation, migration, and invasion of different mucocutaneous cell lines in vitro. Methods Samples of early‐stage tumors (T1‐T2N0M0) from 63 patients with OSCC and CSCC were obtained, in addition to eight normal mucosa and skin tissues from healthy subjects. Oral‐cavity‐derived highly aggressive HSC‐3, less invasive SAS, and HPV‐transformed benign IHGK as well as C‐ha‐ras‐transformed (HaCat) skin carcinoma II‐4 and non‐invasive A5 cell lines were used. Flagellin‐induced mucocutaneous cell lines were compared by using BrdU‐proliferation, scratch migration, and myoma organotypic invasion assays. Results TLR‐4 expression was similar in OSCC and CSCC tumors. TLR‐5 was more abundant in OSCC than in CSCC samples. Flagellin induced the proliferation of SAS, II‐4 and A5, migration of IHGK, II‐4 and A5, and the invasion of II‐4 cells. It had no effect on HSC‐3 cells. Conclusions Flagellin, a TLR‐5 agonist, induced the migration and invasion of less aggressive mucocutaneous cell lines, but it had no effect on the most invasive oral carcinoma cells. The more aggressive clinical behavior of OSCC compared to CSCC may partially be related to the differences in the expression of TLR‐5 in these malignancies.